Breeding API (BrAPI), a standardized RESTful Web Service API Specification for plant breeding data, that enables exchanging data across systems and applications - CGIAR Excellence in Breeding Platform (2021)
TThe Breeding Management System and Breedbase already use it to exchange data as well as integrate independently developed tools that also adhere to the BrAPI standard. EBS has added BrAPI enablement to its development blueprint.